A new pet for myeloma - Dimopoulos, M.-A.; Moulopoulos, L.A.; Terpos, E. (Blood, 2009)
In this issue of Blood, Bartel and colleagues report the independent predictive value of the PET/CT and of the FDG suppression before transplantation in newly diagnosed myeloma patients who were treated using the TT3 regimen.